MENANGKAP MOTIVASI PAHLAWAN PENDIDIKAN (Studi pada Guru Titak Tetap Madrasah Aliyah Kota Pekalongan) - Sofarudin, Akhmad; Djastuti, Indi (Diponegoro Journal of Management, 2014)
Teacher as one component in teaching and learning activities, has an important role in determining the success of learning. Teachers are required to have expertise, responbility, and voluntary social service above personal interests. However teachers have to complete their duties professionally, they still face much problem, especially non official teachers, such as their wealth and clarity of employment status.This study aims to determine the motivation of teachers, especially intrinsic motivation factors which influence non official teachers. Beside, it will determine whether the teachers has prosocial motivation.This study uses qualitative methodsin which data collections was done by observation so as to dig deeper into teaching profession. This study places temporary teachers who have work experience of more than three years of teaching in Madrasah Aliyah both public and private in pekalongan city. The result obtained from this study is temporary teachers motivation influenced by factorsof work values, individual attitudes towards work, goals and expectations, as well as the ability of an individual. It also shows that prosocial motivation is the dominant motivation of temporary teachers.